2012
DOI: 10.1002/ange.201200466
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Alternating Current in Response to Discontinuous Illumination by Photoelectrochemical Cells Based on Photosynthetic Proteins

Abstract: Proteinbasierte photoelektrochemische Zellen, die unter Verwendung eines photosynthetischen Reaktionszentrums (links) hergestellt wurden, erzeugen konventionellen Gleichstrom bei kontinuierlicher Bestrahlung und Wechselstrom bei regelmäßigen Licht‐An/Licht‐Aus‐Zyklen (rechts). Der Mechanismus der Wechselstromerzeugung nutzt die Fähigkeit der natürlichen Reaktionszentren zur Ladungsspeicherung und zur Katalyse hocheffizienter photochemischer Ladungstrennung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 50 publications
5
38
0
Order By: Relevance
“…2b , black). The transient reverse current observed after turning off the excitation light is probably due to dissipation of stored charges in the system, as discussed previously 16 45 . Measurements with monochromatic excitation showed that the current amplitude tracked the absorbance spectrum of the RC in the near infrared ( Fig.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…2b , black). The transient reverse current observed after turning off the excitation light is probably due to dissipation of stored charges in the system, as discussed previously 16 45 . Measurements with monochromatic excitation showed that the current amplitude tracked the absorbance spectrum of the RC in the near infrared ( Fig.…”
Section: Resultssupporting
confidence: 61%
“…The particular Rba. sphaeroides RC used in the present work has been efficiently interfaced with unfunctionalized gold electrodes 15 , used to generate direct or alternating photocurrents 15 16 and in addition to photovoltaics per se it has been used for applications such as biosensing 17 .…”
mentioning
confidence: 99%
“…There is a large interest in substituting natural redox carriers (cytochrome and quinones) by inorganic carrier matrices, which are able to donate/accept electrons to/from the RC as secondary electron donors/acceptors. These functional redox active bionanohybrid materials are promising models for photoelectric energy conversion in either optoelectronic or photovoltaic devices (for reference see, e.g., [59][60][61][62], details are given in the forthcoming paragraphs).…”
Section: Photosynthetic Systems In Bionanotechnologymentioning
confidence: 99%
“…1a, and see Fig. S1 in Supporting information) facilitates a highly-efficient photochemical charge separation that has been exploited for the construction of prototype solar cells [5], [6], [7], photoelectrochemical cells [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18] and biosensors [19], [20]. Reaction centres from oxygenic phototrophs are of particular interest with regard to solar fuel synthesis through water splitting [21], [22] and the powering of catalysis by other redox proteins in non-native, hybrid systems [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…sphaeroides reaction centres incorporated into photoelectrochemical cells [5], [6], [7], [10], [18], [19]. Deposition of this protein on electrode surfaces in such systems is usually achieved by drop-casting or binding from solution, processes which give limited control over protein orientation at the electrode surface and even less control over packing of protein on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%